Understanding the relationship between growth and employment in Nigeria - Olu Ajakaiye; Afeikhena T. Jerome; David Nabena; Olufunke A. Alaba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study examines the relationship between growth and employment in Nigeria to gain insights into the country's paradox of high economic growth alongside rising poverty and inequality. The methodology adopted is the Shapley decomposition approach, complemented with econometric estimation of the country's employment intensity of growth. The findings indicate that Nigeria's growth over the last decade has been 'jobless' and sustained largely by factor reallocations rather than productivity enhancement. Labour reallocations have been mainly from agriculture and manufacturing towards the low productive services sector. Employment elasticity of growth was positive and quite low, reflecting the country's poor overall employment generation record, especially in manufacturing.
Keywords: E24; J21; O47; P52; 330; employment; growth; poverty; employment elasticity; growth decomposition; Nigeria